The housing policy of depoliticization: neoliberal governance, technocracy and urban struggles. The case of the Ukamau Settlers Movement, Estación Central - Paulsen Espinoza, Alex (Investigaciones Geográficas, 2020)
The housing policy has acted as a sedative for the vulnerable sectors, depoliticizing them and transforming them into beneficiary subjects. Under a theoretical framework that considers the characteristics of neoliberal urban governance, with a focus on the technocracy that characterizes it, this study tries to describe a case where the inhabitants faced such neoliberal governance and its technocracy. Through a methodology that considered semi-structured interviews, participating ethnography and data from official organizations, the results show that this technocratic neoliberal governance has established technical intermediaries -such as the Real Estate Management Entities, EGIS- that have limited and made up the participation of the residents. In addition, a high percentage of these Real Estate Management Entities carry out the activities of the technocratic culture: consultancies and consultancies. Likewise, this study tries to account for the strategies carried out by the families of residents of the Ukamau movement to confront these agents, and that it was not only urban protests in public space, but something that went further.